Movement Behaviors and Mental Wellbeing: A Cross-Sectional Isotemporal Substitution Analysis of Canadian Adolescents - Brown, Denver M. Y.; Kwan, Matthew Y. W. (Frontiers in Behavioral Neuroscience, 2021)
Background: Studies have shown reallocating screen time for healthy movement behaviours such as physical activity and sleep can provide important benefits for mental health. However, the focus on positive aspects of mental health such as wellbeing has received limited attention, particularly among adolescents. The purpose of this study was to examine the effects of reallocating physical activity, screen time, and sleep on mental wellbeing in adolescents. Methods: This study involved cross-sectional analysis of data from Wave 1 of the ADAPT study. A total of 1,118 Canadian adolescents enrolled in grade 11 classes (Mage = 15.92; 54.5% female) self-reported their movement behaviours using the International Physical Activity Questionnaire – Short Form to assess moderate-to-vigorous physical activity and daily recall questionnaires to assess recreational screen time and sleep. Participants also completed three measures of mental wellbeing: the Flourishing Scale, Rosenberg Self-Esteem Scale, and a brief Resiliency scale from the Canadian Campus Wellbeing Survey. Results: Isotemporal substitution analysis revealed replacing 60 minutes of screen time with either moderate-to-vigorous physical activity or sleep has significant benefits for mental wellbeing. Comparatively, reallocating 60 minutes between moderate-to-vigorous physical activity and sleep does not impact mental wellbeing. Discussion: Findings suggest healthy movement behaviours confer similar beneficial effects for adolescent’s mental wellbeing. Health promotion campaigns targeted towards adolescents should consider highlighting that reallocation of screen time to either sleep or moderate-to-vigorous physical activity may provide important benefits for mental wellbeing.